Design and Evaluation of Functional Gummies with Cognitive-Enhancing Brahmi Extract (International Journal of Scientific Research in Science and Technology, 2026)
The increasing demand for functional and nutraceutical foods has stimulated the development of value-added confectionery products with enhanced health benefits. The present study aimed to formulate and evaluate nutraceutical gummies enriched with natural fruit extracts of amla (Emblica officinalis), guava (Psidium guajava), and pomegranate (Punica granatum), along with Brahmi extract (Bacopa monnieri), a well-known medicinal herb recognized for its cognitive-enhancing and neuroprotective properties. Fructooligosaccharide (FOS) was incorporated as a low-calorie functional sweetener to provide prebiotic benefits and improve sensory acceptability. The gummies were formulated using optimized concentrations of gelling agents and bioactive components to achieve desirable physicochemical and organoleptic properties. The developed formulations were evaluated for moisture content, pH, and texture profile, along with sensory attributes such as color, flavor, taste, and overall acceptability. The results indicated that the optimized formulation exhibited satisfactory textural quality, good storage stability, and high sensory acceptance. The incorporation of fruit-derived antioxidants and Brahmi extract significantly enhanced the functional and therapeutic potential of the product without adversely affecting its palatability. Therefore, the developed nutraceutical gummies can serve as an effective delivery system for bioactive compounds, with promising applications in the functional food and nutraceutical industries.